Specific and non-specific timing abilities of elite Polish hurdlers - Mehlich, R.; Iskra, J.; Goralczyk, R.; Waskiewicz, Z. (Journal of Human Kinetics, 2002)
The sense of rhythm of lower limbs of elite Polish hurdlers was diagnosed with the use of the Vienna Test System. The research project was conducted on 13 male and 10 female elite athletes with the control group consisting from 17 female and 21 male students of Academy of Physical Education aged 20-23 years who never practiced any sport discipline professionally. The experimental subjects were elite Polish hurdlers with European Championships medallists, Olympic Games and World Championships participants. Authors determined that there is no sexual dimorphism between hurdlers in timing performance evaluated with the use of specific and nonspecific rhythms. There are also no statistically significant differences in timing abilities between elite Polish hurdlers and students of physical education. The acquired results suggest great attention and caution during evaluation of professional elite athletes co-ordination.